African-American Women's Suffering In Alice Walker's The Color Purple (1982) Novel: A Feminist Approach - Darmawanti, Denik Fajar (2012)
The major problem of this study is how African- American women's suffering is reflected in The Color Purple novel by Alice Walker. The objective of this study is to analyze the novel based on structural elements and to analyze the novel based on feminist approach. In analyzing The Color Purple novel, the writer uses qualitative method and feminist approach. The object of the study is Alice Walker's The Color Purple novel published in 1982. The data sources consist of primary data and secondary data sources. The primary data sources is The Color Purple novel itself and the secondary data sources are the other sources related to the analysis such as books of literary theory, the author's biography, and the other relevant information to analysis of this research. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, from the structural analysis of the novel, it shows that Alice Walker wants to express her idea about how women are suffered by their society that is caused by the whites and black men. Second, based on Feminist Approach, the conclusion is that there is African - American women's suffering in the Alice Walker's The Color Purple novel. Walker creates that unfair treatment will always result rebellion. Third, this novel presents the social construction that women who have suffering and pains in their lives can transform their lives to a better life.